Heart rate reserve at ventilatory thresholds, maximal lactate steady state and maximal aerobic power in well-trained cyclists: training application - Morán-Navarro, R.; Mora-Rodriguez, R.; Rodriguez-Rielves, V.; De la Fuente-Pérez, P.; Pallarés, J. G. (European Journal of Human Movement, 2016)
Introduction: Several physiological tests have been developed to predict cycling performance. However, the high costs and expertise needs to perform these tests detracts coaches and athletes from using them habitually. The aim of this study is to provide the equivalence between these physiological assessments and heart rate reserve (HRR) to facilitate training advice to cyclists. Materials and Methods: Thirty three aerobically-trained male cyclists ( O2max 62.1±4.6 ml·kg-1·min-1) performed two graded exercise tests (GXT; 50 W warm-up followed by 25 W·min-1) to exhaustion. O2 and CO2 data were collected throughout GXT and several continuous tests were performed to detect maximal lactate steady state workload (MLSS). Results: VT1, VT2 and O2max were achieved at power outputs of 184±36, 298±36 and 390±34 W, respectively corresponding with 66±9, 88±6 and 100% of HRR. MLSS (n=14), occurred at 256±31 W. These HRR defined five training zones; 53-62% HRR (zone R0), 62-71% HRR (zone R1), 74-86% HRR (zone R2), 86-99% HRR (zone R3) and 100% HRR (zone R3+). Discussion: We found the HRR correspondence to ventilatory aerobic and anaerobic thresholds (i.e., VT1 and VT2) MLSS and O2max. Those HRR defined 5 distinguishable training zones corresponding to those physiological events that could be used for optimizing training.